GENDER-BASED DOPAMINE REGULATION AND TREATMENT OUTCOMES IN ADULTS AGED 18-40 UNDERGOING COGNITIVE BEHAVIORAL THERAPY AND PHARMACOTHERAPY AT KHYBER TEACHING HOSPITAL, PESHAWAR (The Research of Medical Science Review, 2024)
Objective: This study investigates gender-based differences in treatment outcomes and dopamine regulation among adults (ages 18-40) undergoing Cognitive Behavioral Therapy (CBT) and pharmacotherapy at Khyber Teaching Hospital, Peshawar, focusing on how gender influences neurochemical changes and symptom reduction in anxiety and depression. Materials and Methods: A quantitative approach was employed, involving 300 participants (150 males and 150 females), who underwent either CBT or pharmacotherapy for 12 weeks. The study assessed gender differences in symptom relief (anxiety and depression) and changes in dopamine levels, both pre- and post-treatment, using psychological measures and neurochemical analysis. Results: Both CBT and pharmacotherapy showed effectiveness in reducing anxiety and depression. However, treatment responses and dopamine regulation varied by gender. The CBT group demonstrated the most significant reductions in anxiety (45%) and depression (47%). Males in the pharmacotherapy group showed the most rapid reduction in anxiety (41%) by week 8. Post-treatment dopamine levels in females of the CBT group showed a considerable increase, reaching 49.1 ng/mL, which was significantly higher than that observed in other groups. Conclusion: The findings emphasize the importance of considering gender in the development of personalized mental health treatment strategies. Gender-based differences in treatment efficacy and dopamine regulation indicate the need for gender-specific interventions to optimize outcomes for both males and females. This research contributes to the growing evidence supporting tailored approaches in mental health care.